Penelitian pengaruh stabilizer BaCd kompleks terhadap sifat fisis kompon PVC untuk acuan sepatu - Sunarso Hs (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1986)
Ba Cd a material used as a stabilizer. By adding Ba Cd stabilizer to the plastics compound in this experiment will avoid degradation wich makes the physical properties of the compound lower.The research proved that Ba Cd causes the compound unchanged the properties of impact strength after the compound gets heat treatment.The applicate of 4,5% Ba Cd stabilizer improved the quality of the compound for last making.